Pembuatan Sistem Informasi Administrasi Kerja Praktek dan Pengabdian Masyarakat Berbasis Website - Fawaz Najib Risal, Muhammad; Ambarsari, Nia; Sutoyo, Edy (CV RIFAINSTITUT, 2022)
Practical Work and Community Service (KPPM) is one of the compulsory subjects at the Faculty of Industrial Engineering at Telkom University. In practice, practical work and community service are a learning process to work in a company/institution/institution with the aim of gaining work experience. The Faculty of Industrial Engineering is one of the faculties at Telkom University which has a vision to become research and entrepreneurship that plays an active role in the development of knowledge in the field of information technology-based industrial systems that contribute to the national economy. However, the Faculty of Industrial Engineering has problems in managing practical work administration and community service, but this study only discusses the Student module. Previously, the obstacles faced by students in the administrative process of practical work and community service were starting from receiving information related to their supervisor only through excel files that were distributed on social media to scheduling the presentation of practical work reports and community service who had to contact their supervisor via social media. The system is considered less effective and efficient and there is no practical work administration system and community service, so there is a need for an Information System for practical work and community service based on this website which aims to assist the administrative process of practical work and community service students at the Faculty of Industrial Engineering who in making systems This website-based information system uses the Laravel framework and MySQL database with the Extreme Programming method, besides that this website-based information system is tested using blackbox testing and usability testing methods. The results of the blackbox testing functional testing of the system can run as expected, as for the results of usability testing. Based on the respondents' answers, an average score of 78 was obtained. Based on the results obtained from the position obtained, it can be said that the practical work administration and community service webiste is in the category good for use by students.